ONLY LOVE KNOWS HOW TO TEACH (CIPEEX, 2022)
ACCESSIBILITY GOES BEYOND GUARANTEEING THE RIGHT TO BECOME ATTRACTIVE TO A CONDITION OF PHYSICAL OR PSYCHIC WEAKNESS. THIS TERM IS STILL MISUNDERSTOOD. IN ADDITION, THIS IS ONE OF THE REPORTS OF GUARANTEE OF FREE CONTACT, INTERACTION AND SOCIALIZATION, AS WELL AS THE FREEDOM OF ACCESS TO OTHERS AND THE FREEDOM TO INTERACT WITH THEM. THE PRESENT WORK WAS COMPOSED OF TWO SONGS THAT REPRESENT LOVE, EMPATHY, BROTHERHOOD AND FRATERNITY, QUALITIES THAT ARE INTRINSIC AND EVERYDAY. CULTURAL POSES ARE METHODS THAT GUIDE THE MOMENTS OF INTROSPECTION, GENERATING A METAMORPHOSIS OF PERSONALITIES. THE TWO SONGS CHOSEN WERE VOCALIZED LIVE, IN A SIX-MINUTE INTERVAL, WITH THE SCOPE OF A SPECIAL MOMENT. FOR EXAMPLE, A PRESENTATION SOUGHT TO EMPHASIZE FREE INTERPERSONAL RELATIONSHIPS, WITHOUT RESTRICTIONS AND DIFFERENCES, WAS NOT A LEARNING CHANNEL BUT A SOLUTION THAT HINDERS UNDERSTANDING FOR PERSONAL EMPOWERMENT.KEYWORDS: LOVE.TEACHING. LEARNING.